DEFINING MINIMAL IMPORTANT DIFFERENCES AND ESTABLISHING CATEGORIES FOR THE FRAILTY INDEX. (11th November 2018) - Eendebak, R; Theou, O; van der Valk, A; Godin, J; Andrew, M; McNeil, S; Rockwood, K
Abstract: We aimed to define minimal clinically important differences (MID) in the Frailty Index (FI) and to establish FI categories (FIc) in two clinical and three population cohorts. Data came from the Survey of Health, Ageing, and Retirement in Europe (SHARE: n = 29851, median age in years [range]: 63.0 [50.0–104.0]), the Canadian Study of Health and Ageing (n = 5516, 80.0 [70.0–104.0], the National Health and Nutrition Examination Survey [n = 3146, 66.0 [50.0–85.0], the Older Patient Information Database [n = 912, 81.0 [56.0–103.0], and the Canadian Immunization Research Network Serious Outcomes Surveillance Network (SOS: n = 6063, 80.0 [65.0–105.0]). FIs were constructed using the deficit accumulation approach. MIDs were defined by Cohen's effect sizes and bootstrapping analysis. The FIc were determined by Clinical Frailty Scale (CFS) levels and validated by stratum-specific likelihood ratios (SSLRs) against adverse health outcomes. The most conservative MID in the FI across the cohorts was 0.03 [95% CI: 0.03, 0.03]. Results remained similar when stratified by age and sex. The FIc identified based on the CFS was <0.20, 0.20–0.30, 0.30–0.40, >0.40. The FIc displayed a dose-response relationship with ≥2 weeks of hospitalization (e.g. SHARE SSLRs: 0.491 [95% CI: 0.448, 0.536], 1.017 [0.908, 1.154], 1.746 [1.472, 2.035], 2.620 [2.276, 3.051]) and mortality (e.g. SOS SSLRs: 0.500 [95% CI: 0.442, 0.556], 0.924 [0.819, 1.033], 1.733 [1.486, 1.980], 3.264 [2.825, 3.722]). Identifying the MID in the FI and establishing the FIc can assist with using frailty as an outcome in interventional studies.